2017
DOI: 10.1245/s10434-017-5883-6
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy for Recurrent Melanoma: A Multicenter Study

Abstract: SLNB can be successful in patients with LR/IT melanoma, even if prior SLNB was performed. In this population, the rates of SLNB positivity and nonsentinel node metastases were 40% and 37%, respectively. SLNB may guide management and prognosis after LR/IT disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…An additional consideration for the surgeon is to perform SLNB for an in‐transit or satellite lesion given our group has reported a 40% rate of SLNB positivity in those patients . At the time of that publication, the only adjuvant therapy approval was for ipilimumab which required 1 mm of SLNB involvement.…”
Section: Applying Trial Results To Clinical Practicementioning
confidence: 99%
“…An additional consideration for the surgeon is to perform SLNB for an in‐transit or satellite lesion given our group has reported a 40% rate of SLNB positivity in those patients . At the time of that publication, the only adjuvant therapy approval was for ipilimumab which required 1 mm of SLNB involvement.…”
Section: Applying Trial Results To Clinical Practicementioning
confidence: 99%
“…Thus, in one recent study of patients who developed limited local resectable recurrence between 2005 and 2014, only 31% developed distant metastasis while 29% died of melanoma during the follow-up period (40). This finding has been reproduced in several other studies (41,42). This is not dissimilar from the death rate from stage III primary melanoma (40).…”
Section: Discussionmentioning
confidence: 67%
“…The median DMFS was 23 months for those staged node negative by clinical examination only, and 5 months for those with synchronous macroscopic nodal disease . A recent review of three institutions experience found similar findings; progression free survival of 6 years in the SLN negative group and 1.4 years in the SLN positive group and OS of 83% and 57%, respectively ( P = 0.06) …”
Section: Introductionmentioning
confidence: 67%
“…For the bulk of patients who are clinically node negative, micrometastasis can be identified in the regional lymph nodes in approximately 30% to 50% of patients. A recent review of four series, including 203 patients undergoing SLNB for IT disease reported a positive SLN in 39% and 36% had additional positive lymph nodes at completion lymph node dissection . Although IT disease alone is adequate to consider systemic therapy, for the clinically node‐negative patients, SLNB can further stratify patients into two fairly distinct prognostic groups (N1 vs N2 or N3 disease) which could have an impact on the decision for adjuvant systemic therapy.…”
Section: Introductionmentioning
confidence: 99%